Development and Evaluation of Gastroretentive Floating Bilayer Tablets Containing Ivabradine hydrochloride and Trimetazidine dihydrochloride (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Unlike conventional angina treatment medicines, newer antianginals such as Ivabradine hydrochlorideand Trimetazidine dihydrochloride displayed therapeutic potential without negative effects. However, IBH andTMZ both have shorter half-life and require multiple dosing. Literature study revealed that bilayer tablet ofcombination is not available. Hence, the objective of present research was to formulate and evaluate bilayer floatinggastroretentive tablets with IBH immediate and TMZ floating release layer. Materials and Methods: Simpledirect compression method and floating technique was employed. IBH and TMZ layer developed separately.IBH layer prepared using Avicel-112, Klucel EXF ultra, and Vivasol/Crosscarmelose sodium while TMZlayer developed using Kollidon SR, Benecel K 200 M, and Sodium bicarbonate. Best trials combined for thepreparation of bilayer tablet. Tablets evaluated for pre-compression and post-compression parameters, floatingtime, floating lag time (FLT), total floating time swelling index, and matrix integrity. Results: Melting point,differential scanning calorimetry, and ultraviolet absorbance confirmed the identity and purity of drug. Fouriertransform infrared spectrum of active pharmaceutical ingredient and drug mixture with excipients demonstratedthe compatibility. IR layer trial I-4 showed passable flow with 3 s of disintegration time in distilled water and100% drug release within 5 min. Floating layer trial T-8 showed fair flow characteristic, 15 s FLT, >24 h of totalfloating time and controlled the drug release more than 12 h without burst effect. Discussion: Preformulationstudy result revealed that the both the drug are pure form and compatible. For immediate release layer, Vivasol(Crosscarmelose) showed best disintegration and combination HPMC K200 M and Kollidon SR polymer withsodium carbonate provided controlled release with low FLT and high total floating time. Conclusion: Based onresearch findings, it can be concluded that bilayer gastroretentive tablets successfully formulated with IBH as IRlayer and TMZ as floating layer. Combination of polymer needed for drug release control with tablet floatability.Hydrophilic polymer Benecel K200 M forms matrix channel which entrap sodium bicarbonate bubbles and tabletbecome buyant while Kollidon SR and stearic acid contributes in retardation of drug release.